Cognitive linguistics and second language acquisition of Chinese theories and applications - Wu, Shu-Ling; Huang, Lihong; Polley, Carl (Cambridge University Press, 2024)
Although cognitive processes are fundamental in shaping the language that we speak, they are often overlooked in language teaching and learning. This groundbreaking book addresses how to use key cognitive linguistic (CL) concepts to analyze the Chinese language and to advance L2 Chinese teaching and learning. It presents an overview of the most prominent CL research published in both Chinese and English and explores how it applies to L1 and L2 Chinese studies. Including sample lesson plans and classroom activities, it demonstrates to language teachers how to use CL-based approaches to explain and teach a wide range of linguistic phenomena to their students. Researchers will also gain new insights from the summaries of recent advances and contrastive analyses between English and Chinese. Covering up-to-date research, yet written in a clear and engaging style, it will foster a new understanding of teaching and learning Chinese